Motivação no serviço público: o caso dos servidores técnico-administrativos do Centro de Educação, Campus I, Universidade Federal da Paraíba - Araújo, Edseuda Pereira Marques (2018)
The present research aims to know the main factors that influence the motivation of the technical-administrative servers of the Education Center of the Federal University of Paraíba in their work environment. For that, a survey was made on the main concepts related to motivation, taking as reference the studies developed by Alderfer (1969), McClelland (1972), Herzberg (1997), Douglas McGregor (1999), Maslow 2012), among others. The research is part of the quantitative-qualitative approach. The research subjects were the technical-administrative servants of the Education Center who joined before and after the implementation of the Restructuring and Expansion Program of the Federal Universities REUNI. For data collection, a questionnaire was applied to a sample of 72% of the total number of technical-administrative servers. The results indicated that the factors that contributed to motivation in the work environment of the servers are: recognition and appreciation of their activities by peers, good relationship with peers and the very condition of being a public servant. The factors identified as having the least contribution to motivation are the lack of material resources, the lack of commitment of some servers and the shortage of servers in some sectors. Finally, in addition to the suggestions presented by the present study, the respondents proposed, among other actions, improvements in infrastructure, training and planning of managers regarding activities carried out in the sectors of the Education Center.